Methodological framework to collect, process, analyze and visualize cyber threat intelligence data - Amaro, Lucas José Borges (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.